Editorial Welcome to the IEEE Open Journal of the Solid-State Circuits Society (OJ-SSCS) - Firooz Aflatouni; Lucien Breems; Edoardo Charbon; Qinwen Fan; Hossein Hashemi; Antonio Liscidini; Woogeun Rhee; Stefan Rusu; Jae-Sun Seo; Jerald Yoo; Kathy Wilcox; Eugenio Cantatore (IEEE Open Journal of the Solid-State Circuits Society, 2021)
Dear Readers, The editorial board is pleased to welcome you to the IEEE Open Journal of the Solid-State Circuits Society (OJ-SSCS). Our first papers will soon be available online via the IEEEXplore® platform.